Investigation on the Mechanical and Microstructural Characteristics of Diffusional Bonded Gray Cast Iron and Low Carbon Steel - Baharudin, B.A. (Springer Science and Business Media Deutschland GmbH, 2022)
An investigation has been made of the diffusional bonded couples of gray cast iron and low carbon steel that has been subjected to heat treatment. The objective is to establish the post bond heat treatmentâs parameters influence on the mechanical and structural properties of the diffusional bonded couples. The tensile strength of the diffusion bonded joints was found to be increased with increased heat treatmentâs temperature and time. The microstructural examination has also shown that at higher heat treatment temperature and time also had resulted in microvoids and interface lines to be disappeared, and the bond/weld at the interfaces of the diffusional welded couples seemed to be more complete. Correspondently, these resulted in the increased of the tensile strength. The microhardness value at the interface lines of the joints was found to be increased, while the charpy impact strength value was on the opposite way with the increased heat treatment temperature. The microstructural analysis has also shown that much thicker diffusion layers of spherodization zone and carbon rich zone were formed at higher temperature at the interfaces of the joints. These are also correlated with the microhardness and the charpy impact values obtained at higher temperature. These results were in consistent with the principle and theory of diffusion bonding whereby at higher temperatures, more activation energy is available for atoms inter-diffusion to take place, while with longer time, it allows higher volume of diffusion of atoms, and hence it changes the behavior of the joints. Thus, heat treatmentâs temperature and time were found to have a strong influence on the mechanical and microstructural characteristics of the diffusion bonded gray cast iron and low carbon steel. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.